Quantitative Assessment of PALB2 and BRIP1 Genes Expression in the Breast Cancer Cell Line under the Influence of Tamoxifen: PALB2 and BRIP1 Genes Expression under Tamoxifen - Kharrati-Koopaee, Hamed; Heydari, Seyed Taghi; Dianatpour, Mehdi; Bagheri Lankarani, Kamran (Galen Medical Journal, 2023)
Background:Breast cancer is considered one of the leading causes of mortality in the world. Cancer incidence and consequently, drug consumption can strongly influence gene expressions at the transcriptome level. Therefore, the assessment of the candidate biomarkers’ gene expression can accelerate the diagnosis process and increase the chance of treatment and remission. In this regard, the quantitative assessment of Partner and localizer of BRCA2 (PALB2) and BRCA1 Interacting Helicase 1 (BRIP1) genes expression in the breast cancer cell line under the treatment of Tamoxifen (TAM) was executed in this study. Materials and Methods :MCF7 cells were cultured as TAM-treated and control groups. RNA extraction and cDNA synthesis were performed based on the instructions of provided kits. qPCR Hi-ROX Master Mix kit was applied to the Quantitative Real-Time Polymerase Chain Reaction (Q-PCR). The outputs of Q-PCR were analyzed by REST statistical software. Results:Outcomes derived from data analysis of BRIP1 gene expression did not show any significant difference between the gene expression of control and TAM-treated groups. The expression of PALB2 was significantly higher in the TAM-treated group compared to the control group (P<0.05). Conclusion:Our findings showed a significant alteration between PALB2 gene expression in the TAM-treated breast cancer cell line and the control cell line. The quantitative assessment of mentioned genes as possible markers could be considered a non-invasive method for breast cancer in the processes of prognostic evaluations, screening, and treatment monitoring.